Asuhan Kebidanan Continuity of Care (COC) pada Ny. S Umur 38 Tahun di RS Gondo Suwarno - Lestari, Sri; Isfaizah (Universitas Ngudi Waluyo, 2024)
Continuity of care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborn care and family planning services that connect women's health needs in particular and the personal circumstances of each individual. The type of research used is descriptive, with a case study approach. Data collection techniques used are using primary data and secondary data. Primary data is obtained through interviews, observations and physical examinations, and documentation using SOAP. While secondary data is data obtained from the KIA book. The sample is a pregnant woman in the third trimester of pregnancy, 40 weeks 4 days G3P2A0. The results of care obtained in Mrs. S, 38 years old, G3P2A0, 40 weeks 4 days of pregnancy with physiological pregnancy, labor took place normally and complementary actions were given in the form of Couterpressuer massage, the postpartum period took place normally, no bleeding, good contractions, lochia rubra. Perineal wounds are abraded on the skin of the perineum, and in newborns there are no signs of abnormalities, during the care given to Mrs. S's baby, the care given is in accordance with the baby's needs such as monitoring weight, early and on-demand breastfeeding, prevention of infection, prevention of heat loss, umbilical cord care. Providing IEC about newborn care, and about mandatory immunization. Mrs. S decided to use the Coper T IUD, so as not to interfere with the production and quality of breast milk. Conclusion The care given to Mrs. S is in accordance with midwifery care standards from pregnancy to family planning, as well as the provision of complementary care given is Couterpressuer Massage. This Couterpressuer Massage has been proven to reduce pain during contractions in the first stage, making the mother more comfortable and more relaxed when facing the labor process. Abstrak Continuity of care dalam kebidanan adalah serangkaian kegiatan pelayanan yang berkelanjutan dan menyeluruh mulai dari kehamilan, persalinan, nifas, pelayanan bayi baru lahir serta pelayanan keluarga berencana yang menghubungkan kebutuhan kesehatan perempuan khususnya dan keadaan pribadi setiap individu. Jenis penelitian yang digunakan yaitu deskriptif, dengan pendekatan studi kasus Teknik Pengumpulan data yang digunakan adalah menggunakan data Primer dan data sekunder. Data Primer diperoleh melalui wawancara, observasi dan pemeriksaan Fisik, serta dokumentasi menggunakan SOAP. Sedangkan data Sekunder data yang diperoleh dari buku KIA. Sample adalah seorang ibu hamil trimester III Usia Kehamilan 40 Minggu 4 hari G3P2A0. Hasil asuhan yang didapat Pada Ny.Sumur 38 Tahun G3P2A0 usia kehamilan 40 minggu 4 hari dengan hamil fisiologis, persalinan berlangsung secara normal dan diberikan Tindakan komplementer berupa pijatan Couterpressuer, masa nifas berlangsung secara normal, tidak ada pendarahan, kontraksi baik, lochea rubra. Luka perineum lecet dikulit perineum, dan pada bayi baru lahir tidak ada tanda-tanda kelainan/abnormal, selama diberikan Asuhan pada bayi Ny.S, Asuhan yang diberikan sesuai dengan kebutuhan bayi seperti pemantauan berat badan, pemberian ASI secara dini dan on demand, pencegahan infeksi, pencegahan kehilangan panas, perawatan tali pusat. Memberikan KIE tentang perawatan BBL, dan tentang imunisasi wajib. Ny. S memutuskan untuk menggunakan KB IUD Coper T, agar tidak menganggu produksi dan kualitas ASI. Kesimpulan Asuhan yang diberikan pada Ny.S sudah sesuai dengan standar asuhan kebidanan mulai dari hamil hingga KB, Adapun pemberian asuhan komplomenter yang diberikan yaitu Pijat Couterpressuer. Pijat Couterpressuer ini terbukti dapat untuk mengurangi nyeri saat kontraksi pada kala 1, membuat ibu lebih nyaman dan lebih rileks pada saat menghadapi proses persalinan.